Dietary diversity as a food security indicator - Hoddinott, John F.; Yohannes, Yisehac (International Food Policy Research Institute, 2002)
Household food security is an important measure of well-being. Although it may not encapsulate all dimensions of poverty, the inability of households to obtain access to enough food for an active, healthy life is surely an important component of their poverty. Accordingly, devising an appropriate measure of food security outcomes is useful in order to identify the food insecure, assess the severity of their food shortfall, characterize the nature of their insecurity (for example, seasonal versus chronic), predict who is most at risk of future hunger, monitor changes in circumstances, and assess the impact of interventions. However, obtaining detailed data on food security status—such as 24- hour recall data on caloric intakes—can be time consuming and expensive and require a high level of technical skill both in data collection and analysis. This paper examines whether an alternative indicator, dietary diversity, defined as the number of unique foods consumed over a given period of time, provides information on household food security. It draws on data from 10 countries (India, the Philippines, Mozambique, Mexico, Bangladesh, Egypt, Mali, Malawi, Ghana, and Kenya) that encompass both poor and middle-income countries, rural and urban sectors, data collected in different seasons, and data on calories acquisition obtained using two different methods. ....[D]ietary diversity would appear to show promise as a means of measuring food security and monitoring changes and impact, particularly when resources available for such measurement are scarce.